Peningkatan Peran Masyarakat dalam Pencegahan KDRT Melalui Penyuluhan Anti Kekerasan Berbasis Gender - Cintami Farmawati (Muwazah, 2018)
The research of participatory aims to increase community participation in prevention of domestic violence, through counseling against gender based violence. Research location in Semarang. Data collection techniques using direct observation, interviews with counseling participants, pre test and post test. The results of the analysis show that, there is an increase in people's knowledge and understanding of the Law on the Elimination of Domestic Violence, the situation of gender based violence and the problem of assistance and government programs in the elimination of gender based violence. In addition, there is a change in attitude shown through participant participation in activities, the ability to explain and describe the material that has been conveyed by the resource person, conveying ideas and thoughts about the steps and solutions that can be done in removing gender-based violence, and then domestic violence. Therefore, a religious approach should be developed to reduce religious fundamentalism which is detrimental to women in various extension, socialization, campaign and other activities